Molecular dynamics simulations of membrane proteins. - Biggin, P; Bond, P (2008)
Membrane protein structures are underrepresented in the Protein Data Bank (PDB) because of difficulties associated with expression and crystallization. As such, it is one area in which computational studies, particularly molecular dynamics (MD), can provide useful additional information. Recently, there has been substantial progress in the simulation of lipid bilayers and membrane proteins embedded within them. Initial efforts at simulating membrane proteins embedded within a lipid bilayer were relatively slow and interactive processes, but recent advances now mean that the setup and running of membrane protein simulations is somewhat more straightforward, although not without its problems. In this chapter, we outline practical methods for setting up and running MD simulations of a membrane protein embedded within a lipid bilayer and discuss methodologies that are likely to contribute future improvements.